Fundamentals of structural steel design - Gambhir, M.L. (Chennai McGraw Hill Education, 2013)
Fundamentals of Structural Steel Design presents the basic principles of structural steel design in a simple, practical, logical and cogent manner for the proper understanding of students. It conforms to the limit states design method as given in the latest revision of IS: 800-2007. The book is intended to develop the ability to analyze and design structural elements subjected to different types of forces.
Keywords: Civil Engineering; IS 800:2007